Clima Laboral de la Coordinación General Administrativa Financiera de la Universidad Nacional de Loja durante el Tercer Trimestre del 2016 - Vallejo Figueroa, Xiomara Nathaly (2017)
The operation of a comprehensive institution in general, requires a work climate environment, where they provide to managers and employees of a pleasant working environment, and for that reason it was determined the working environment of the Financial General Administrative Coordination of the National University of Loja, during the third quarter of the year 2016; which consists of a review of the literature which described the fundamental theories and concepts to analyze both the organizational dimensions, such as personal information within the work environment. The research aims to determine the labor climate of Financial Administrative Coordination of the National University of Loja, during the third quarter of the year 2016, on the basis of organizational dimensions outlined by the authors, Sara Coral & Jaime pereña (2009). It is worth mentioning, the importance of this research work as such, is to inform the public servers that make up the Administrative Coordination, which is the financial perspective on the labor climate in which they operate. Finally, within these results, it can be concluded that public servants have a neutral response to the organizational dimensions, while both within the personal dimensions that are, Involvement, Self-realization, Relationships, Address, there is a negative response, as it is taken as the fundamental Interpersonal Relations, which affects the servers in the development of their functions, which determines that there is a negative work environment in the Financial Administrative Coordination